Faktor- Faktor yang berhubungan dengan Kejadian Balita Bawah Garis Merah (BGM) di Puskesmas Way Hitam IV Kec Belitang Jaya Kab OKU Timur - Muryatiningsih, Nanik; Sukarni, Diah; Riski, Meriska (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The problem of nutrition is still a challenge in improving public health throughout the world, especially in developing countries, especially in Indonesia. Based on the Indonesian Nutrition Status Study through monitoring the growth of toddlers on the nutritional status of toddlers which shows the percentage of BGM in Indonesia has increased in 2019 by 17.9%, in 2020 it has increased to 19.6% and in 2021 it has decreased again 17, 7%. The purpose of this study was to determine the relationship between mother's knowledge, diet and family income simultaneously with the Incidence of Under-fives Under the Red Line (BGM) at the Way black IV Health Center. The type and research design is quantitative using analytic survey method with cross sectional approach. The population in this study were all mothers with toddlers aged 12-59 months who visited the in the working area of the Way black IV Health Center, totaling 1,557 toddlers. The sample used amounted to 94 respondents. The results of the univariate analysis obtained from 94 respondents, 16 respondents (17.0%) experienced BGM and 78 respondents (83.0%) did not experience BGM. The results of the chi-square statistical test obtained ρ value = 0.000 less than α = 0.05 indicating that there is a significant relationship between mother's knowledge, eating patterns and family income with the incidence of under-fives under the red line (BGM) in the working area of the Way Hitam IV Health Center